The small molecule curcumin analog FLLL32 induces apoptosis in melanoma cells via STAT3 inhibition and retains the cellular response to cytokines with anti-tumor activity - Young Gregory S; Fossey Stacey L; Hoyt Dale G; Lin Jiayuh; Abdelhamid Dalia; Schwartz Eric B; Benson Don M; Bakan Courtney; Yui Jennifer; Li Chenglong; Fuchs James R; Bill Matthew A; et al. (Molecular Cancer, 2010)
Abstract Background We characterized the biologic effects of a novel small molecule STAT3 pathway inhibitor that is derived from the natural product curcumin. We hypothesized this lead compound would specifically inhibit the STAT3 signaling pathway to induce apoptosis in melanoma cells. Results FLLL32 specifically reduced STAT3 phosphorylation at Tyr705 (pSTAT3) and induced apoptosis at micromolar amounts in human melanoma cell lines and primary melanoma cultures as determined by annexin V/propidium iodide staining and immunoblot analysis. FLLL32 treatment reduced expression of STAT3-target genes, induced caspase-dependent apoptosis, and reduced mitochondrial membrane potential. FLLL32 displayed specificity for STAT3 over other homologous STAT proteins. In contrast to other STAT3 pathway inhibitors (WP1066, JSI-124, Stattic), FLLL32 did not abrogate IFN-γ-induced pSTAT1 or downstream STAT1-mediated gene expression as determined by Real Time PCR. In addition, FLLL32 did not adversely affect the function or viability of immune cells from normal donors. In peripheral blood mononuclear cells (PBMCs), FLLL32 inhibited IL-6-induced pSTAT3 but did not reduce signaling in response to immunostimulatory cytokines (IFN-γ, IL 2). Treatment of PBMCs or natural killer (NK) cells with FLLL32 also did not decrease viability or granzyme b and IFN-γ production when cultured with K562 targets as compared to vehicle (DMSO). Conclusions These data suggest that FLLL32 represents a lead compound that could serve as a platform for further optimization to develop improved STAT3 specific inhibitors for melanoma therapy.